Kinetic Monte Carlo model of an organic solar cell calibrated by experiments - Wilken, Sebastian; Upreti, Tanvi; Dahlström, Staffan; Persson, Gustav; Kemerink, Martijn (nanoGe - NGFM19, 2019)
Kinetic Monte Carlo (kMC) simulations have been proven to be a valuable tool to model transient extraction and mobility measurements on organic photovoltaics (OPVs) [1]. However, it is much more difficult and computationally demanding to model the key characteristic of any OPV device, its current-voltage (IV) curve under illumination. To describe a complete IV curve, the kMC model must also acc...